Stability of retained austenite in high carbon steel under compressive stress: An investigation from macro to nano scale - Hossain, R.; Pahlevani, F.; Quadir, Md Zakaria; Sahajwalla, V. (Nature Publishing Group, 2016)
Although high carbon martensitic steels are well known for their industrial utility in high abrasion and extreme operating environments, due to their hardness and strength, the compressive stability of their retained austenite, and the implications for the steels' performance and potential uses, is not well understood. This article describes the first investigation at both the macro and nano scale of the compressive stability of retained austenite in high carbon martensitic steel. Using a combination of standard compression testing, X-ray diffraction, optical microstructure, electron backscattering diffraction imaging, electron probe micro-analysis, nano-indentation and micro-indentation measurements, we determined the mechanical stability of retained austenite and martensite in high carbon steel under compressive stress and identified the phase transformation mechanism, from the macro to the nano level. We found at the early stage of plastic deformation hexagonal close-packed (HCP) martensite formation dominates, while higher compression loads trigger body-centred tetragonal (BCT) martensite formation. The combination of this phase transformation and strain hardening led to an increase in the hardness of high carbon steel of around 30%. This comprehensive characterisation of stress induced phase transformation could enable the precise control of the microstructures of high carbon martensitic steels, and hence their properties.